PENYULUHAN MENGENAI ASPEK HUKUM PENGELOLAAN DESA WISATA YANG BERKEADILAN DI DESA GIRI MADIA, KECAMATAN LINGSAR, KABUPATEN LOMBOK BARAT - I Gusti Agung Wisudawan; Budi Sutrisno; Diman Ade Mulada; L. Achmad Fathoni (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
This article focuses on the management of tourist village destinations with the aim of controlling or organizing various resources successfully in order to achieve targets, economic growth and income with services to tourists as well as environmental protection and preservation of tourist attractions, which of course will be very beneficial for society and fairly. The legal materials used are Primary Legal Materials, namely Law Number 10 of 2009 concerning Tourism, Law Number 25 of 2000 concerning the National Development Program (VAT), NTB Regional Regulation Number 2 of 2016 concerning Halal Tourism. Secondary Legal Materials, namely literature and Scientific articles related to the problems raised in this research. The legal material collection technique used in this research is Documentation Study with Legal Material Analysis, namely Qualitative Descriptive Analysis with deductive conclusions. The result of this legal education activity is that the people of Giri Madia Village have an understanding and awareness regarding the management of Tourism Villages and have made village regulations regarding Tourism Startup Villages